Sonographic Assessment of Carotid Arteries in Adults with Radiographic Features of Hypertensive Cardiomegaly at Kano, North Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Hypertension is a chronic medical condition in which there is elevation of arterial blood pressure (s). Hypertensive cardiomegaly is a complication and effect of long standing systemic hypertension on the heart.Aims:This study is to relate a component of hypertensive heart disease with sonographic changes found in the carotid arteries of these patients, as they are directly linked to atherosclerotic effect of hypertension.Materials and Methods:In this prospective crosssectional study, four hundred (400) subjects with primary hypertension were recruited. The study group (200) is having cardiomegaly on PA chest radiograph. The carotid arteries of all participants were insonated on both gray scale and Doppler modes. Demographic characteristics, CIMT, and Doppler velocimetric indices (PSV, EDV, and RI) were generated and subjected to statistical analysis.Results:The mean age for the study group was 48.91 ± 10.0, consisting of 110 (53.9%) males and 90 (45.9%) females. Cardiothoracic ratio was seen to increase with age (P< 0.0001) and not associated with gender (P= 0.110). The mean carotid intimamedia thickness (CIMT) in the right and left was 1.3 ± 0.13 mm and 1.50 ± 0.18 mm, with the highest CIMT of 1.70 ± 0.25 mm seen at higher systolic readings (P= 0.002). Mean PSV of right common carotid artery (CCA) was 66.20 ± 21.81 cm/s and left CCA was 59.54 ± 22.75 cm/s, EDV of right CCA was 17.85 ± 5.97 cm/s and left CCA was 16.56 ± 6.44 cm/s, RI of right CCA was 0.72 ± 0.07 cm/s and left CCA was 0.72 ± 0.06 cm/s. Positive correlation was seen between age and CIMT (P= 0.001). 7.5% had echogenic smooth plaques.Conclusions:Carotid artery abnormalities continue to relate with severity of hypertension among patients with chest radiographic findings.